Panel Discussion - Ermanno Malaspina; Andrea Balbo; Katarzyna Marciniak; Jerzy Axer; Marcus Janka; David Movrin (Ciceroniana On Line, 2020)
The panel discussion was moderated by Prof. Jan Miernowski (Faculty of “Artes Liberales”, University of Warsaw/Department of French & Italian, University of Wisconsin-Madison).